Improving taxation environment: Attracting foreign direct investment - R. R. Singh (Indian Council for Research on International Economic Relations (ICRIER), 2016)
With opening of the economy in 1991 and subsequent removal of regulatory and trade barriers, India became an attractive investment (Foreign Direct Investment-FDI) destination. A large number of multinationals have established operations in India to utilise the services of available skilled manpower. Indian tax administration was always perceived to be difficult. The economic liberalisation had created challenges in integrating Indian tax system with the world economy during the adjustment phase. World financial environment had remained depressed since 2008. The actions of the government in the area of taxation laws during 2012 and 2013 with sudden introduction of General Anti-Avoidance Rules (GAAR) including retrospective amendment to law further aggravated the taxation environment specially in the area of international taxation. This badly affected the sentiments of the international investor community. In other words it can be said that the economic liberalization did not match with the tax aggressiveness and that probably led to some major concerns, and impacted ease of doing business. Though the government did take some steps during 2012 and 2013 and further more steps during 2014 and 2015 to soothe the investor sentiment, there are still areas of persisting concern which need to be addressed. Section one, introduction, broadly deals with the concerns of the multinationals in the area of taxation environment. Section two deals with the genesis of the recent crisis in this area and issues involved such as introduction of GAAR, international taxation, retrospective amendment dispute resolution etc. Section three deals with GAAR. Section four deals with various issues involved in the area of international taxation including Permanent Establishment, attribution of profits, transfer pricing, taxation of Information Technology (IT) and Information Technology enabled Services (ITeS) sectors, Advance Pricing Agreements (APAs) and Safe Harbour Rules. While Section five deals with retrospective amendments to the Income Tax Act and Section six deals with various aspects of dispute resolution, section seven deals with attitude of the tax administration. Section eight deals with the recent steps taken to address the taxation issues and section nine contains the conclusions and the areas that still needs to be addressed.
Keywords: F21; G11; H25; H26; K34; K41; O15; P45; 330; GAAR; International Taxation; Transfer Pricing; APAs; Safe Harbour Rules; Retrospective Amendments and Dispute Resolution